Tampering with Cell Division by Using Small‐Molecule Inhibitors of CDK–CKS Protein Interactions. Issue 3 (23rd January 2015) - Hamdi, Amel; Lesnard, Aurélien; Suzanne, Peggy; Robert, Thomas; Miteva, Maria A.; Pellerano, Morgan; Didier, Bruno; Ficko‐Blean, Elizabeth; Lobstein, Annelise; Hibert, Marcel; Rault, Sylvain; Morris, May C.; et al.
Abstract Cyclin‐dependent kinases (CDKs) control many cellular processes and are considered important therapeutic targets. Large collections of inhibitors targeting CDK active sites have been discovered, but their use in chemical biology or drug development has been often hampered by their general lack of specificity. An alternative approach to develop more specific inhibitors is targeting protein interactions involving CDKs. CKS proteins interact with some CDKs and play important roles in cell division. We discovered two small‐molecule inhibitors of CDK–CKS interactions. They bind to CDK2, do not inhibit its enzymatic activity, inhibit the proliferation of tumor cell lines, induce an increase in G1 and/or S‐phase cell populations, and cause a decrease in CDK2, cyclin A, and p27Kip1 levels. These molecules should help decipher the complex contributions of CDK–CKS complexes in the regulation of cell division, and they might present an interesting therapeutic potential.